Color Terms and Verbal Signs in Women Skin Care Product Online Advertisement - Paxia Ichsan, Ferida (Humanis; Vol 22 No 3 (2018)DO - 10.24843/JH.2018.v22.i03.p21, 2018)
The title of this study is “Color Terms and Verbal Signs in Women Skin Care Product Online Advertisement” . The aims of this study are to find out the color terms and verbal sign, to describe the meaning and function of color and verbal signs, and their relationships that are found in three different women skin care product of the online advertisements. The data of this study were taken from three different websites of women skin care namely www.ponds.com, www.bioderma.com and www.laneige.com. Documentation method and the qualitative method were used in this study. There are three theories applied in this study, the first theory is theory of sign by Saussure cited in Chandler 2001 in order to analyze the meaning of color terms and verbal signs.The second theory is the theory of meaning and function proposed by Leech (1974) was used in order to find out the meaning and function of color terms' role and the verbal signs on each advertisement which also supported by the theory of color meaning symbolism proposed by Morton (1997). The results shows that there is a strong relationship between colors and verbal signs' role on each advertisement which supported by the model illustration in order to give impression for the readers to but the product.